Analysis of Electric Conductivity Variance in the Insulation of HVDC Cables - Bhaumik, Palash (My University, 2025)
Power cables with insulation based on cross-linked polyethylene (XLPE) are used in high voltage direct current (HVDC) onshore and offshore power grids to transmit large amounts of electric energy over long distances. One of the important aspects to be considered when designing the insulation system of such cables is the variation of the electric conductivity of the insulation material in radial direction between the energized conductor and grounded screen. Since the conductivity of XLPE is dependent on electric field strength and temperature, predicting its actual changes in the cable is challenging and typically is done based on some empirical formulas. These, however, do not take into account the effect of the diffusion of impurities and byproducts introduced into the material during the manufacturing process on conductivity variations. In the thesis, the electric conductivity of XLPE was measured using material samples taken from continuous peelings of the insulation of a real cable. This allowed for examining its field and temperature dependencies at different distances from the conductor, i.e. at different contents of byproducts. The experimentally obtained material properties were further utilized as input for a computer model, which was developed to analyze the dynamics of space charge accumulation and corresponding electric field in the cable. The results outlined in the thesis are essential for improving the design rules for HVDC cables to ensure their reliable and safe operation.